2007
DOI: 10.1002/lt.21300
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of severe ventricular arrhythmias during pulmonary artery catheterization in liver allograft recipients

Abstract: Liver allograft recipients may develop a hyperdynamic circulation and cardiac electrophysiologic abnormalities. The incidence of severe ventricular arrhythmias in liver allograft recipients during pulmonary artery (PA) catheterization was determined. One hundred five liver allograft recipients were studied prospectively; 5 of the patients with preexisting valvular heart disease, ischemic heart disease, or arrhythmias were excluded. Severe ventricular arrhythmia, defined as 3 or more consecutive ventricular pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 15 publications
(15 reference statements)
0
36
0
Order By: Relevance
“…Nevertheless, there is no evidence that PAC improves outcome in the perioperative and critical care setting [3]. Gwak et al [4] reported in a series of 105 patients undergoing OLT an incidence of 70% arrhythmias during PAC insertion. Of these, 33% were classified as benign and 37% classified as severe arrhythmia (defined as three or more consecutive premature ventricular beats occurring at a rate of 100 bpm).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, there is no evidence that PAC improves outcome in the perioperative and critical care setting [3]. Gwak et al [4] reported in a series of 105 patients undergoing OLT an incidence of 70% arrhythmias during PAC insertion. Of these, 33% were classified as benign and 37% classified as severe arrhythmia (defined as three or more consecutive premature ventricular beats occurring at a rate of 100 bpm).…”
Section: Discussionmentioning
confidence: 98%
“…This minimizes the risk of PA perforation through inadvertent catheter "wedging." Prolonged catheterization time also is a recognized risk factor for ventricular arrhythmias during PAC insertion, 5,6 and excessive insertion length is the major contributing factor to catheter knotting. Hence, the use of fluoroscopy during PA insertion in cardiac surgery patients at higher risk of a PAC-related complication is a pragmatic, rational, and feasible intervention to minimize complications.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The PAC however, might be inaccurate if it is not positioned correctly and may not reflect changes in intravascular volume rapidly enough. With reported hazards of PAC insertion like ventricular arrhythmias, 13 and due to availability of less invasive monitoring tools, the use of PAC is declining. It is now increasingly reserved, for those cases where there is a suspicion of porto pulmonary hypertension, 14 as severe pulmonary hypertension (mPAP > 45) is associated with high perioperative mortality and, if not successfully treated, is a contraindication to LT. 15 Standard hemodynamic monitoring, such as arterial pressure monitoring, can also be extended for the assessment of CO, preload and afterload.…”
Section: Hemodynamic Monitoringmentioning
confidence: 99%